Performance of ggbs concrete in strength development and durability / A. Jelani ... [et al.] - Jelani, A.; Diah, A.B.M; Ridzuan, A.R.M; Kamarulzaman, K.B (2002)
This paper deal with an investigation on the performance of concrete containing ground granulated blast furnace slag (GGBS) as a partial cement replacement. The three engineering properties are compressive strength, oxygen permeability and water absorption. In addition chloride content in concrete immersed in sea-water was tested. Tests were conducted on concrete in which 40 and 60 percent (by-weight) of OPC was replaced hy GGBS. Water cementitious (w:c) ratio of 0.4 was used for all mixes. Whilst w:c ratio of 0.5 was used for compressive strength, oxygen permeability and water absorption specimens. Concrete moist cured at 20°C, 27°C, cured at site and cured in sea-water were tested at ages between three days and one year for compressive strength. Water absorption, permeability and porosity tests were conducted for samples cured at 28 days, 180 days and 1 year. it was found that one year the compressive strength of moist cured concrete with w:c 0.4 containing 40% GGBS is significantly higher in comparison with the control, whilst specimens cured at other condition performed comparably with the control. It was found that specimens with w:c = 0.5 containing GGBS produce lower compressive strength than the control. However, it is comparable with the control beyond 120 days. It was found that w:c ratio of 0.4 produces lower permeability in comparison with w:c = 0.5. However all permeability values lie between the "high" and "low" permeability regions. The results also showed that with increasing age, the compressive strength of concrete increases. However the permeability and absorption values decreased with age.